2015
DOI: 10.1111/pops.12314
|View full text |Cite
|
Sign up to set email alerts
|

The Backyard Politics of Attitudes Toward Immigration

Abstract: Using two survey experiments, I reconsider the role that the racialized physical traits and level of assimilation of salient immigrants play in shaping attitudes toward immigration. In the first experiment, a nationwide sample of 767 White, non-Latino adults was exposed to a story about a family of undocumented immigrants living in the Unites States who were at risk of deportation. Subjects were randomly assigned to view a version of the story in which the immigrants were depicted with light skin and stereotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(30 citation statements)
references
References 66 publications
2
28
0
Order By: Relevance
“…For example, it would be important to know if, as some studies suggest, nonverbal effects are stronger for certain political outcomes than for others. At least two studies find that political visuals have a stronger impact on behavioral intentions than on attitudes (Ostfeld, 2015;Powell et al, 2016) behavior during political events. The picture of a Syrian boy washed away on the sea shore in the fall of 2015 generated an outpour of collective sympathy worldwide; the distribution of this picture, and the public behavioral response that followed was strongly facilitated by social media.…”
Section: Discussion This Body Of Evidence On the Moderators Of Nonvementioning
confidence: 99%
“…For example, it would be important to know if, as some studies suggest, nonverbal effects are stronger for certain political outcomes than for others. At least two studies find that political visuals have a stronger impact on behavioral intentions than on attitudes (Ostfeld, 2015;Powell et al, 2016) behavior during political events. The picture of a Syrian boy washed away on the sea shore in the fall of 2015 generated an outpour of collective sympathy worldwide; the distribution of this picture, and the public behavioral response that followed was strongly facilitated by social media.…”
Section: Discussion This Body Of Evidence On the Moderators Of Nonvementioning
confidence: 99%
“…Likewise, Fetzer (2011) analyzed several data sets, including the General Social Survey (GSS), World Value Survey (WVS), and American National Election Studies (ANES) data, and found that cultural and economic threats significantly affected public attitudes toward immigrants in the U.S. In addition, there have been many studies which focused on immigrants' characteristics that could be considered deleterious to the host population, such as limited English proficiency (Adida et al, 2010;Sniderman et al, 2004), closed-minded attitude (Adida et al, 2010;Brader et al, 2008;Valentino & Iyengar, 2011), low economic status (Harell, Soroka, Iyengar, & Valentino, 2012;Ostfeld, 2017;Sniderman et al, 2004), and low levels of education (Adida et al, 2010;Hainmueller & Hiscox 2010;Harell et al, 2012). Of course, not all immigrants possess such characteristics (Aleksynska & Tritah, 2015;Cortes, 2004), but information produced and shared from studies may contribute to citizens' negative perceptions.…”
Section: Public Attitudes Toward Immigrantsmentioning
confidence: 99%
“…Ethnocentrism, the preference of one's own racial or ethnic group above others, is an important predictor of immigration views, as are right‐wing authoritarianism and social dominance orientation (Kinder and Kam, 2009; Banks, 2016; Craig and Richeson, 2013; Thomsen, Green, and Sidanius, 2008). Ostfeld (2015) found evidence that attitudes can vary according to the degree to which immigration is presented as a racial issue. Using a survey experiment, that study asked white respondents questions about immigration after presenting images of newcomers with different racialized physical traits.…”
Section: Literaturementioning
confidence: 99%